Possibilities and Limitations in the Biomechanical Analysis of Countermovement Jumps: A Methodological Study - Kibele, A. (Journal of Applied Biomechanics, 1998)
Possibilities and limitations in the biomechanical analysis of countermovement jump performance were examined using force plate data. Four male and 4 female sport students participated in the study. Software designed to test jumping performance was used to evaluate recordings from a force plate and to compute net velocity and net displacement measures for the center of gravity. In parallel, a film analysis incorporating Dempster`s center of gravity model was used for a comparison. Validity of the computed kinetic measures was evaluated with a general analysis of the major error sources including the data acquisition and numerical computations. Numerical integration procedures were found to be a reasonable tool for calculating net velocity and net displacement parameters for a more detailed analysis of athletic jumping performance. On the other hand, it appeared that Dempster-like center of gravity models can cause errors that disqualify their use as validation criteria for kinetic parameters.